Abstract Number ‐ 63: A swine model to simulate the mechanism of aspiration thrombectomy. - Timothy Shimizu; Ichiro Yuki; Zachary W Hsu; Hemdeep Kaur; Earl Steward; Shuichi Suzuki (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Aspiration thrombectomy is an effective technique to recanalize large vessel occlusions (LVO) in stroke patients and has become one of the major techniques. Advancements in technology have enabled the use of catheters with larger lumens and higher aspiration forces; however, the successful reperfusion rate of the first pass remains at 57–63%. This poses a question as to why this rate is still suboptimal when conducting aspiration thrombectomy. We established a swine model for LVO, which provides concurrent fluoroscopic and transmural visualization of real‐time vessel responses during aspiration thrombectomy, to investigate the mechanism of aspiration thrombectomy. Methods Under general anesthesia, a common carotid artery (CCA) and a superficial cervical artery (SCA) of Yorkshire swine (n = 3) were surgically exposed, and an LVO was reproduced by injecting a radiopaque clot analog via a guiding catheter. Each target artery was treated using aspiration catheters with different inner diameters (0.058, 0.068, and 0.088 inches). The CCA group (n = 7) represented large diameter vessels (4‐5mm) simulating a human ICA, and the SCA group (n = 6), with bifurcations, represented small diameter vessels (2‐3mm) simulating a human MCA. To make a consistent clot location in the CCA group, mild, non‐flow‐limiting stenosis was created using a 4‐0 Prolene suture. Fluoroscopy and a high‐resolution digital microscope camera were used simultaneously to monitor angiographic and transmural vessel behavior during the procedure. Average vessel diameter, local blood pressures proximal and distal to the occlusion site, the presence or absence of vessel collapse / reverse flow during the procedures, and pre‐and post‐angiographic findings were evaluated. Results Both fluoroscopic and transmural visualization of mechanical thrombectomy was achieved in all vessels allowing the observation of real‐time arterial wall and clot response during the procedure. The mean blood pressures distal and proximal to the occlusion site showed no significant differences between the two groups. With remote aspiration, all vessels in the SCA group (Mean Diameter: 2.34 ± 0.49mm) showed immediate vessel collapse, and regardless of the lumen size of the catheter, they all failed to recanalize the vessels. Effective clot ingestion was achieved only when direct contact aspiration was applied (5 of 6 vessels). None of the vessels in the CCA group (Mean Diameter: 5.16 ± 0.54 mm) showed vessel collapse during remote aspiration. Six out of 7 vessels (85.7%) treated with remote aspiration showed local reverse flow followed by complete aspiration when the tip of the aspiration catheter was placed 5–20mm away from the clot. One CCA vessel required direct contact aspiration to achieve clot ingestion. Conclusions This swine model to analyze vessel behavior during aspiration thrombectomy may help us understand the mechanism of aspiration thrombectomy. The model may contribute to improving the techniques and the development of new aspiration devices.